A curved-grid gas proportional scintillation counter instrumented with a 25-mm active-diameter photosensor - Monteiro, C. M. B. (2004)
The curved-grid technique provides a simple method to compensate for the variation in solid angle viewed by the PMT in large-area gas proportional scintillation counters (GPSC), improving their performance. The scintillation region is delimited by a planar grid and a curved one, whose shape is calculated to produce a radially increasing scintillation yield, compensating for the decrease in the solid angle. In this work, we applied this technique to a GPSC instrumented with a PMT having a 25-mm diameter photocathode. The maximum ratio of the detector entrance window to the photocathode diameter thus far achieved, without significant performance degradation, is 1.